A Model for E-voting Systems Evaluation - Dasso, Aristides (2011)
This work presents a model for the evaluation of electronic voting systems (evoting). Although these systems are used more and more there have been reports of different kind of problems, underlining the need of having models for their evaluation. The model we present here is based primarily on the Logic Score of Preference (LSP) method, and the requirements are taken from the requirements developed by the Technical Guidelines Development Committee of the Election Assistance Commission of the United States. An overview of the LSP method is given as well as the reasons behind the decision to choose these requirements.